PROBLEMATIKA EKSEKUSI PUTUSAN PENGADILAN TERHADAP PERUSAHAAN PERKEBUNAN YANG TERKENA DENDA GANTI KERUGIAN GUGATAN LINGKUNGAN HIDUP - Wibawa Sitanggang, Riko (Honeste Vivere, 2025)
Several palm oil plantation companies have filed for voluntary bankruptcy through commercial offers to avoid the burden of environmental fines due to environmental lawsuit fines. Instead of paying the fines, the company's assets after being calculated are not enough to pay the fines, let alone the company's operational costs such as mortgage credit, employee wages, and tax payments. As a result, an event of no benefit occurs due to environmental fines for the plantation company. The above events finally encouraged me to write this law by analyzing several regulations, court decisions, legal events that occurred, and of course based on the theory of Radburgh's benefits and continuous development, especially in the field of natural resources and palm oil commodities, especially for palm oil plantation companies that have been subject to environmental fines but their company assets are insufficient and in the end the plantation company filed for voluntary bankruptcy through a commercial permit.